Increased risk for cardiovascular disease in patients with obstructive sleep apnoea syndrome‐chronic obstructive pulmonary disease (overlap syndrome). (8th September 2019) - Voulgaris, Athanasios; Archontogeorgis, Kostas; Papanas, Nikolaos; Pilitsi, Eleni; Nena, Evangelia; Xanthoudaki, Maria; Mikhailidis, Dimitri P.; Froudarakis, Marios E.; Steiropoulos, Paschalis
Abstract: Introduction: Accumulating evidence suggests that cardiovascular disease (CVD) is highly prevalent among patients with concurrent obstructive sleep apnoea syndrome (OSAS) and chronic obstructive pulmonary disease, otherwise known as overlap syndrome (OS). Objectives: The aim of this study was to investigate the 10‐year risk for CVD in OS patients compared with OSAS patients and controls. Methods: Consecutive patients, referred for symptoms suggestive of OSAS, were evaluated with polysomnography and pulmonary function testing. Cardiovascular risk was assessed using the Framingham risk score (FRS) and systematic coronary risk evaluation (SCORE). Results: Overall, 244 participants (184 males) without CVD and diabetes were divided into 3 groups: controls ( n  = 63), OSAS ( n  = 139) and OS ( n  = 42). Both FRS and SCORE were found to be elevated in the OS group compared with the OSAS and control groups ( P  < .001 for all). In multivariate analysis, age ( β  = .461, P  < .001), forced expiratory volume in first second ( β  = −.285, P  = .036) and oxygen desaturation index (ODI) ( β  = .234, P  = .007) were major determinants for the SCORE, whereas age ( β  = .308, P  < .001) and apnoea‐hypopnoea index ( β  = .252, P  = .010) for the FRS. Conclusion: In our study, an increased risk for CVD was observed in a group of patients with OS at the time of their initial evaluation. Further studies are needed in the field of OS in order to investigate, prevent and manage early CVD in this population.